2015
DOI: 10.1186/s12909-015-0524-x
|View full text |Cite
|
Sign up to set email alerts
|

Academic leagues: a Brazilian way to teach about cancer in medical universities

Abstract: BackgroundPerformance of qualified professionals committed to cancer care on a global scale is critical. Nevertheless there is a deficit in Cancer Education in Brazilian medical schools (MS). Projects called Academic Leagues (AL) have been gaining attention. However, there are few studies on this subject. AL arise from student initiative, arranged into different areas, on focus in general knowledge, universal to any medical field. They are not obligatory and students are responsible for the organizing and plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
22

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 25 publications
0
6
0
22
Order By: Relevance
“…Sendo assim, Ligas Acadêmicas são capazes de desenvolver habilidades e competências raramente estimuladas no currículo tradicional [10][11][12][13] , incluindo papel social, papel na prática médica, liderança, gestão, empreendedorismo, inovação, educação em saúde e construção da cidadania 14 , características trabalhadas tanto durante os atendimentos da Liga quanto durante a gestão da diretoria da Liga, que durante um ano cuida de sua organização. Portanto, o desenvolvimento e o incentivo de Ligas Acadêmicas nos currículos inovadores permitem treinamento necessário para que alunos de diferentes graduações em saúde, incluindo graduação em Medicina, adquiram habilidades necessárias para fornecer cuidados de alta qualidade em diferentes modelos de assistência médica 15 .…”
Section: Discussionunclassified
“…Sendo assim, Ligas Acadêmicas são capazes de desenvolver habilidades e competências raramente estimuladas no currículo tradicional [10][11][12][13] , incluindo papel social, papel na prática médica, liderança, gestão, empreendedorismo, inovação, educação em saúde e construção da cidadania 14 , características trabalhadas tanto durante os atendimentos da Liga quanto durante a gestão da diretoria da Liga, que durante um ano cuida de sua organização. Portanto, o desenvolvimento e o incentivo de Ligas Acadêmicas nos currículos inovadores permitem treinamento necessário para que alunos de diferentes graduações em saúde, incluindo graduação em Medicina, adquiram habilidades necessárias para fornecer cuidados de alta qualidade em diferentes modelos de assistência médica 15 .…”
Section: Discussionunclassified
“…Muito mais do que o simples currículo acadêmico moldado pela instituição, o en-gajamento em uma liga permite abranger os horizontes para além da aprendizagem didática. Isso inclui entrar em contato com habilidades administrativas e burocráticas para organização de eventos e motivar a produção do saber científico e o contato com os vários profissionais da área da saúde 5 . O ganho de responsabilidades e a tomada de decisões contribuem para saber lidar com situações adversas e para a formação de perfis de liderança.…”
Section: Visão Gestãounclassified
“…Even though many studies have shown the positive relationship between entrepreneurship education and entrepreneurial intention, there is no consensus on what and how entrepreneurship education actually influences people in practice (Pittaway and Cope, 2007). Besides, some scholars like Oosterbeek et al (2010) find that entrepreneurship education is negatively related to entrepreneurial intention. A critical reason for this contradictory notion is that many scholars treated entrepreneurship education as an undifferentiated whole, ignoring the variety in content and pedagogy in different EEPs (Piperopoulos and Dimov, 2015).…”
Section: Introductionmentioning
confidence: 99%